2012
DOI: 10.2176/nmc.52.892
|View full text |Cite
|
Sign up to set email alerts
|

Serious Adverse Effects of Gamma Knife Radiosurgery for Mesial Temporal Lobe Epilepsy

Abstract: Gamma knife radiosurgery (GKRS) for mesial temporal lobe epilepsy (MTLE) has been proposed as an alternative to surgical resection. We report serious adverse effects of the treatment after follow-up periods over 9 years in 11 patients treated with GKRS between 1997 and 2000. The target volume of the entorhinoamygdalohippocampectomy area was 4.8-17.1 ml. Marginal dose of 20-25 Gy to the 50% isodose was delivered. One patient was drowned after suffering seizure 7 months after GKRS. Two patients did not show any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…A total of 13 studies were included in the meta‐analysis . The characteristics of these studies, the results of which were published between 1999 and 2012, are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 13 studies were included in the meta‐analysis . The characteristics of these studies, the results of which were published between 1999 and 2012, are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of male participants in the included studies ranged from 9.1% to 63.2%, with one study not reporting data on the participants' gender . The study designs also varied: three studies used a retrospective design , six used a prospective design , and the design of four studies was not reported . Most of the studies were single‐arm, except for that of Barbaro and colleagues , which had high‐ and low‐dose arms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other possible complaints have been found such as headache, vomiting, nausea and depression, which may need steroids prescription. Also, complications such as cerebral edema, radiation necrosis, motor deficits, cognitive impairment and cyst formation have been reported 25 .…”
Section: Painmentioning
confidence: 99%
“…With regard to radiosurgery, the possibility for significant post-treatment edema and radiation necrosis exists (108). The benefits of radiosurgery may also be delayed, and the interval between treatment and response can lead to continued seizurerelated functional decline (109). Laser ablation can also lead to damage to surrounding structures and subsequent neurologic sequelae (110).…”
Section: Minimally Invasive Epilepsy Treatmentmentioning
confidence: 99%